1998
DOI: 10.3354/dao034177
|View full text |Cite
|
Sign up to set email alerts
|

Putative spawner-isolated mortality virus associated with mid-crop mortality syndrome in farmed Penaeus monodon from northern Australia

Abstract: Beginning in 1994, farms in northern Australia experienced a higher than normal mortality rate in 12 to 15 g prawns from growout ponds. The farmers named this problem mid-crop mortality syndrome (MCMS). Intramuscular injection of filtered (450 nm), cell-free extracts of moribund prawns from these ponds killed healthy prawns between 5 to 30 d post-injection. A 20 nm virus was visualized by electron microscopy from a 1.4 g ml-l band recovered from caesium chloride gradients of extracts from the moribund prawns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 6 publications
1
34
0
Order By: Relevance
“…The significance of the hypertrophic nuclei in gill epithelium in P. monodon in northern Queensland and their relationship to the similar lesions in Cherax quadricarinatus have yet to be determined. However, Owens et al (1998) have associated a parvo-like virus similar or identical to spawnerisolated mortality virus (SMV) with MCMS. SMV has been associated with lesion similar to those reported here, in myocardium and striated muscle but not in gill epithelium (Fraser & Owens 1996, Owens 1997.…”
Section: Two Moribund Crayfish Collected In June 1998mentioning
confidence: 99%
“…The significance of the hypertrophic nuclei in gill epithelium in P. monodon in northern Queensland and their relationship to the similar lesions in Cherax quadricarinatus have yet to be determined. However, Owens et al (1998) have associated a parvo-like virus similar or identical to spawnerisolated mortality virus (SMV) with MCMS. SMV has been associated with lesion similar to those reported here, in myocardium and striated muscle but not in gill epithelium (Fraser & Owens 1996, Owens 1997.…”
Section: Two Moribund Crayfish Collected In June 1998mentioning
confidence: 99%
“…In northern Queensland farms, 3 of 4 initially affected farms received postlarvae from a single hatchery in January 1994. Once SMV becomes systemic in prawns by breaking through the lamina propria of the gut into the haemocoel, one of the main tissues that become probe-positive are the gonads (Owens et al 1998). This suggests a possible mechanism for vertical transmission from broodstock to postlarvae through infected reproductive tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In situ hybridisation of Penaeus monodon using a gene probe developed for SMV had shown that the major trophic tissue, and usually the first tissue infected, was the gastrointestinal tract (Owens et al 1998). Target organs included the hepatopancreas, midgut caecae, midgut and to a lesser extent, the hindgut caecae.…”
Section: Introductionmentioning
confidence: 99%
“…In situ hybridisation (ISH) using gene probes to SMV (Owens et al 1998), YHV (Tang & Lightner 1999, Tang et al 2002 and GAV (Spann et al 2003) has associated these viruses with histopathology and helped determine their tissue distribution in chronically and acutely infected prawns. In this paper, we have used a sensitive RT-nested PCR test targeted to a region of the MoV M RNA segment with significant homology to the cognate RNA segment of Uukuniemi virus (Cowley et al 2005) to assess its prevalence in Penaeus monodon from eastern Australia.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Due to its commercial importance to these regions, viral diseases of this prawn species have been the focus of intense investigation. Viruses identified in P. monodon from eastern Australia include monodon baculovirus (MBV) (Doubrovsky et al 1988, Belcher & Young 1998, Vickers et al 2000, a lymphoidal parvo-like virus (LPV) (Owens et al 1991), gill-associated virus (GAV) (Spann et al 1995, Cowley et al 1999, 2000a, Smith 2000) and spawner-isolated mortality virus (SMV) (Fraser & Owens 1996, Owens et al 1998. A virus with spherical enveloped particles (74 nm average diameter) has also been detected in eye tissues of moribund farmed prawns (Smith 2000) and although they were slightly larger, some morphological similarity was noted to a reo-like virus detected in Malaysian P. monodon (Nash et al 1988).…”
Section: Introductionmentioning
confidence: 99%